2021
DOI: 10.3389/fmars.2021.768766
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation of Particle Size Distribution in the Kuroshio Region: Possible Causes in the Upper Water Column

Abstract: Particle size distribution (PSD) in the ocean is a fundamental property that influences carbon export and food webs; however, PSD variation and its causes in oligotrophic oceans are not entirely clear. Here, we used Laser In-Situ Scattering and Transmissometry to investigate PSD (size range 5.2–119 μm) and related variables at 11 stations in the surface layer (0–20 m) of the Kuroshio region of the western North Pacific, where strong current causes dynamic hydrographic and ecological conditions. PSD slopes (ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 68 publications
2
5
0
Order By: Relevance
“…accumulation of larger particles detectable by LISST-100X in the presence of a high concentration of TEP, which has a porous, gel-like structure, in the subtropical northwest Pacific along the Kuroshio Current (Yamada et al, 2021). Therefore, porous gellike materials may be a determinant of particle dynamics in subtropical environments.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…accumulation of larger particles detectable by LISST-100X in the presence of a high concentration of TEP, which has a porous, gel-like structure, in the subtropical northwest Pacific along the Kuroshio Current (Yamada et al, 2021). Therefore, porous gellike materials may be a determinant of particle dynamics in subtropical environments.…”
Section: Discussionmentioning
confidence: 99%
“…Among particle properties (POC/PON, Chl a/TPV, POC/TPV, and PON/TPV) within the euphotic layer, only Chl a/TPV showed a significant difference between the two areas (Table 4). Yamada et al (2021) reported that the ratio of TEP concentration, which has a porous gel like structure, to Chl a concentration was elevated in oligotrophic areas along the Kuroshio Current. Low Chl a/TPV in the subtropical gyre may indicate a smaller contribution of phytoplankton to TPV and lower food quality relative to the slope.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations